2020
DOI: 10.3390/medicines7090052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lonicera japonica Flower Bud Extract on Citrobacter rodentium-Induced Digestive Tract Infection

Abstract: Background: Although antibiotic therapy is currently a gold standard for bacterial infections, it is not used for severe diseases like enterohemorrhagic Escherichia coli, in which the Shiga toxin is overproduced by antibiotic action. The Lonicera japonica flower bud (LJF) is an herbal component used against purulent diseases in traditional Japanese and Chinese medicine. We investigated the effects of LJF extract (LJFE) on Citrobacter rodentium-induced digestive tract infection in a mouse model. Methods:Citroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Modern medical pharmacological experiments show that Lonicera japonica has broad-spectrum antibacterial, antiviral, anti-inflammatory, antipyretic, and immune-enhancing effects [ 16 ]. Minami et al have found that Lonicera japonica flower bud extract enhances the phagocytic activity of macrophages, increases the survival rate, and reduces Citrobacter rodentium colonization in Citrobacter rodentium -induced digestive tract infection mouse model [ 17 ]. The polysaccharide extracted from Lonicera japonica exerts neuroprotective effect to improve behavioral changes and inhibit neuronal loss in lipopolysaccharide-induced learning and memory impairment mice [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern medical pharmacological experiments show that Lonicera japonica has broad-spectrum antibacterial, antiviral, anti-inflammatory, antipyretic, and immune-enhancing effects [ 16 ]. Minami et al have found that Lonicera japonica flower bud extract enhances the phagocytic activity of macrophages, increases the survival rate, and reduces Citrobacter rodentium colonization in Citrobacter rodentium -induced digestive tract infection mouse model [ 17 ]. The polysaccharide extracted from Lonicera japonica exerts neuroprotective effect to improve behavioral changes and inhibit neuronal loss in lipopolysaccharide-induced learning and memory impairment mice [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is equally essential as silver may pose adverse effects at high concentrations. 45,46 and thus a combination approach can be used to achieve a similar level of killing at low concentrations. Further, upon studying the possible mechanism of the synergistic effect seen, it was delineated that AgNPs caused cell wall lysis and damage to the cell membrane integrity of E coli cells.…”
Section: Methodsmentioning
confidence: 99%
“…Modern pharmacological research has confirmed the strong antimicrobial activity of L. japonica in vivo and in vitro (Rhee and Lee, 2011;Xiong et al, 2013;Yang et al, 2016;Minami and Makino, 2020;Yan L. et al, 2020). In vitro study showed that L. japonica has antimicrobial effects such as Bacteroides fragilis, Bacteroides ovatus, Clostridium difficile, Clostridium perfringenes, Propionebacterium acnes, Staphylococcus aureus, Shigella, Salmonella, and Escherichia coli (E. coli; Rhee and Lee, 2011;Xiong et al, 2013;Yang et al, 2016Yang et al, , 2018Yan L. et al, 2020).…”
Section: Lonicera Japonica (Extracts) Modulates Intestinal Micobiotamentioning
confidence: 99%
“…In vitro study showed that L. japonica has antimicrobial effects such as Bacteroides fragilis , Bacteroides ovatus , Clostridium difficile , Clostridium perfringenes , Propionebacterium acnes , Staphylococcus aureus , Shigella , Salmonella , and Escherichia coli ( E. coli ; Rhee and Lee, 2011 ; Xiong et al, 2013 ; Yang et al, 2016 , 2018 ; Yan L. et al, 2020 ). In vivo study showed that L. japonica could significantly promote the colonization of beneficial bacteria and inhibit the reproduction of harmful bacteria ( Minami and Makino, 2020 ; Yang X. et al, 2020 ). Wang et al (2014) showed that unfermented or fermented L. japonica both can significant alteration of the distribution of intestinal flora, especially affecting the population of Akkermansia spp.…”
Section: Lonicera Japonica (Extracts) and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation